Age and the Risk of Paclitaxel‐Induced Neuropathy in Women with Early‐Stage Breast Cancer (Alliance A151411): Results from 1, 881 Patients from Cancer and Leukemia Group B (CALGB) 40101. (8th November 2018) - Barginear, Myra; Dueck, Amylou C.; Allred, Jacob B.; Bunnell, Craig; Cohen, Harvey J.; Freedman, Rachel A.; Hurria, Arti; Kimmick, Gretchen; Le‐Rademacher, Jennifer G.; Lichtman, Stuart; Muss, Hyman B.; Shulman, Lawrence N.; et al.
Abstract: Purpose: A few previous studies report a direct relationship between older age and chemotherapy‐induced neuropathy. This study further evaluated this adverse event's age‐based risk. Methods: CALGB 40101 investigated adjuvant paclitaxel (80 mg/m 2 once per week or 175 mg/m 2 every 2 weeks) in patients with breast cancer and served as a platform for the current study that investigated age‐based differences in neuropathy. Grade 2 or worse neuropathy, as per Common Terminology Criteria for Adverse Events version 4, was the primary endpoint; patients were assessed at baseline, every 6 months for 2 years, and then annually for 15 years. Results: Among these 1, 881 patients, 230 were 65 years of age or older, 556 were 55–64 years, and 1, 095 were younger than 55; 1, 226 neuropathy events (commonly grade 1 or 2) were reported in 65% of the cohort. The number of grade 2 or worse events was 63 (27%), 155 (28%), and 266 (24%) within respective age groups ( p = .14). In univariate analysis, only motor neuropathy had a higher age‐based incidence: 19 (8%), 43 (8%), and 60 (5%), respectively ( p = .04); in multivariate analyses, this association was no longer statistically significant. Other endpoints, such as time to onset of neuropathy (time from trial enrollment to neuropathy development) and time to improvement (time from maximal grade sensory neuropathy to a one‐category improvement), showed no statistically significant age‐based differences. In contrast, obesity was associated with neuropathy, and every 2‐week paclitaxel was associated with trends toward neuropathy. Conclusion: Although paclitaxel‐induced neuropathy is common, older age is not an independent risk factor. Clinical trial identification number . NCT00041119 (CALGB 40101). Abstract : Mixed results have been reported regarding whether older cancer patients are at a greater risk for chemotherapy‐induced neuropathy. This article further evaluates the age‐based risk of this adverse event.